Should we judge a mask by its cover?. Issue 7 (July 1992) - Jeffrey, A A; Warren, P M
Abstract : BACKGROUND: A table of the approximate ranges of inspired oxygen delivered at given oxygen flow rates is often given on the packaging of oxygen masks. A study was carried out to check the inspired oxygen concentration given by one of the new masks, which has been designed to be used with or without the Venturi attachment as a result of the proposal to use it without the Venturi attachment as a general purpose mask for emergency use. METHODS: Measurements were made at resting respiratory rate and 26 breaths/min in 12 normal subjects. Continuous oxygen and carbon dioxide concentrations were recorded at the lips with a mass spectrometer, and inspired oxygen concentrations were calculated from end tidal values by means of the alveolar gas equation. Measurements were made at oxygen flow rates of 2, 4, and 6 l/min for the mask alone and at 2 and 4 l/min with both the 24% and the 28% Venturi attachments. RESULTS: Without the Venturi attachment the mask gave average inspired oxygen concentrations 8-10% greater than are stated on the packaging at oxygen flow rates of 2, 4, and 6 l/min at resting respiratory rates of 8-20 breaths/min, some individuals receiving 30% more than expected. Addition of the interchangeable Venturi attachments designed to give 24% and 28% inspired oxygen delivered average concentrations within 2% of the expected concentrations, no individual receiving more than 5% above the expected concentrations. CONCLUSIONS: The labelling on the packaging of oxygen masks may lead to inappropriate use by those not expert in prescribing oxygen therapy. Caution is still needed when a single multipurpose mask is being selected for emergency use, where accurate delivery of low concentrations of oxygen is vital for some patients.